Upaya Kepala Sekolah dalam Membangun Hubungan Harmonis Melalui Gaya Kepemimpinan Demokratis - Didit Darmawan; Mahmudah Mahmudah; Duwi Rahmawati; Rahayu Mardikaningsih; Mila Hariani (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
A harmonious relationship between principals and teachers is a crucial aspect in determining the effectiveness of educational delivery within schools. The leadership style adopted by the principal plays a significant role in shaping the pattern of relationships between principals and teachers. This study aims to examine strategies that can be implemented by democratic principals to build harmonious relationships with teachers. The method used in this study is a literature review, which involves collecting and analyzing various sources of information relevant to the topic. The findings indicate that effective strategies include involving teachers in decision-making processes, fostering open communication, providing opportunities for professional development, and resolving problems through deliberation and mutual discussion. The implementation of these strategies can create a conducive working environment and improve the quality of education provided in schools.